A Competency Standard for Conducting Recruitment Assessment to Enhance Human Resource Development Productivity - Surono (PT. Publikasiku Academic Solution, 2026)
This study develops a competency unit standard for conducting competency-based recruitment assessment in Indonesian organisations. It addresses the absence of such a unit in the national competency framework (SKKNI) and seeks to strengthen HRD productivity through more evidence-based people-placement decisions. The study adopts a qualitative research and development (R&D) design based on the four-phase TAEDES504 framework. The unit was drafted using the Subject-Bold and Range Statement Integration Model, grounded in the author's Interface Model, which requires the grammatical subject of each Performance Criterion to be bolded and matched with a corresponding Range Statement entry. The draft was then validated against N.78SPS01.006.1, the formally endorsed Indonesian standard for NCS verification. The resulting unit, SKK-CKP-AS-01-26, comprises five Elements, 15 Performance Criteria, and 15 fully traceable Range Statement entries, while explicitly integrating all eight employability skills as assessment-method categories. Verification against all six criteria of N.78SPS01.006.1 Element 3 confirmed full conformity, with no Corrective Action Requests required. The paper offers the first formally structured SKKNI unit for competency-based recruitment assessment and contributes a practical, rule-based NCS formulation protocol that ensures bidirectional traceability between Performance Criteria and Range Statements. The protocol is potentially transferable to other competency-based training systems.